Analysis of e-Government Services: A Study of the Adoption of Electronic Tax Filing in Indonesia - Rosdiana Sijabat (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
This study explores the impact of perceived usefulness, perceived ease-of-use, and perceived risks of using electronic tax filing (e-Filing) on the intention to use e-Filing through a technology acceptance model framework. The theoretical foundation used in this study is the technology acceptance model (TAM) on 201 valid questionnaires completed by Indonesian taxpayers. The data collected was analyzed by structural equation modelling using SmartPLS (3.0 Version). The results of the study revealed that e-Filing’s perceived usefulness and risk were significantly associated with intention to use, while perceived ease-of-use did not have a significant effect. Although the influence of perceived risks significantly mediated the influence of perceived usefulness, it did not significantly mediate the influence of ease-of-use. Gender was found to significantly moderate the influence of e-Filing’s perceived usefulness, but not to moderate the influence of perceived ease-of-use. Importance-Performance Matrix Analysis (IPMA) finds that the intention to use e-Filing is most strongly influenced by its perceived usefulness and perceived risk. This implies that policymakers must highlight the perceived usefulness and communicate the perceived risks of e-Filing to ensure taxpayers are willing to use the system. To the best of the author’s knowledge, this study is the first to examine both mediation and moderation to analyze the adoption of technology in Indonesia’s taxation system and offer a policy perspective through IPMA.